PENGARUH SELF-ESTEEM, BUDAYA ORGANISASI DIMEDIASI PERILAKU INOVATIF TERHADAP KINERJA PRAJURIT PADA BATALYON RANRATFIB 1 MENKAV 1 MARINIR JAKARTA - Wirawan, Sigit; Sugiarno, Yuventius (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
This study aims to analyze the influence of self-esteem, organizational culture mediated by innovative behavior on soldier performance in Ranratfib Battalion 1 Menkav 1 Marine Jakarta.. The population in this study is 463 officers serving in the Ranratfib 1 Menkav 1 Marine Battalion Jakarta. This type of research is an explanatory with a quantitative approach.The sampling technique used in this study is multivariate with correlation, so the number of sample members is taken 20 times the number of variables studied. There are 4 variables in this study, so the number of sample members is 20 X 4 variables so that the number of samples is 80 respondents. The data analysis technique of this study uses SEM-PLS. The results of the study show that self-esteem has an effect on innovative behavior. Organizational culture has been proven to have a insignificant effect on innovative behavior. Self-esteem has a positive effect on the performance of soldiers. Organizational culture has a significant positive effect on soldier performance. Innovative behavior has been proven to have an effect on the performance of soldiers. Self-esteem has a significant positive effect on soldier performance through innovative behavior. Organizational culture is proven to have no effect on soldier performance through innovative behavior.